DNA-Related Pathways Defective in Human Premature Aging - Vilhelm A. Bohr (The Scientific World Journal)
One of the major issues in studies on aging is the choice of biological model system. The human premature aging disorders represent excellent model systems for the study of the normal aging process, which occurs at a much earlier stage in life in these individuals than in normals. The patients with premature aging also get the age associated diseases at an early stage in life, and thus age associated disease can be studied as well. It is thus of great interest to understand the molecular pathology of these disorders.